La escritura, un reto en la escuela lenguajes, didácticos y sentires Writing, a challenge from school. Language, didactics and feelings - Sánchez Borrero, Ana Milena (Universidad Santiago de Cali, 2020)
The present writing is born from the reflections of two research works that revolve around the topics of writing and reading in university students and from the conception of teacher training linked to the idea of reverie since Bachelard, from there, it leads to a reflection around the same theme but in the initial stage where the fundamental structures of the subject's constitution processes are woven. In both works, language and didactics are a fundamental part of their livelihood. In these symbiotic relationships between subject, learning, didactics and reverie, the theme of writing is presented in a quest to generate a different idea than to assume it as a purely instrumental process but to unite it with different forms of its approach, and childhood being a time of greater Openness to learning, conceiving writing from these places can make the difference of improving writing processes in later years.